2022
DOI: 10.1038/s41598-022-10511-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing prognostic value of preoperative platelet indexes in patients with resectable gastric cancer

Abstract: The ratio of mean platelet volume (MPV) to count (PC) (MPV/PC) has been applied in the diagnosis and prognosis of various malignancies. However, the prognostic value of MPV/PC in gastric cancer has not been studied yet. This study aims to explore the prognostic value of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), combined neutrophil-platelet score (CNPS), systemic immune-inflammation index (SII) and MPV/PC in patients with resectable gastric cancer. In this study, the medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…MPV/PC was significantly lower in patients with esophageal squamous cell carcinoma than in the control group, and a lower MPV/PC was associated with local progression and a worse prognosis [ 23 ]. Similarly, a lower MPV/PC was associated with poor prognosis in patients with gastric cancer, and MPV/PC has a higher accuracy than NLR or PLR in predicting the prognosis of gastric cancer [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPV/PC was significantly lower in patients with esophageal squamous cell carcinoma than in the control group, and a lower MPV/PC was associated with local progression and a worse prognosis [ 23 ]. Similarly, a lower MPV/PC was associated with poor prognosis in patients with gastric cancer, and MPV/PC has a higher accuracy than NLR or PLR in predicting the prognosis of gastric cancer [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of MPV when treatment applied was also reported in the patients with pancreatic cancer ( 60 , 70 ), squamous cell carcinoma of the esophagus ( 71 ), and gastric cancer ( 72 ). Compared with other clinical covariates (e.g., neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, combined neutrophil-platelet score and systemic immune-inflammation index), the ratio of MPV/platelet count was more accurate in determining the prognosis of gastric cancer patients and could be an independent prognostic factor for patients with resectable gastric cancer ( 73 ). Further, some studies investigated the cause of increased MPV in cancer patients.…”
Section: Clinical Applications Of Platelets For Cancer Patientsmentioning
confidence: 99%
“… 13 , 14 Therefore, the NLR is a prognostic indicator in patients with NSCLC, 5 , 15 , 16 small cell lung cancer, 17 , 18 and other cancers. 19 , 20 , 21 , 22 Specifically, Nathan et al revealed that the NLR is a significant prognostic indicator of survival in patients treated for early‐stage NSCLC with stereotactic radiation. 5 Moreover, patients with stage IV NSCLC 15 with a high NLR were also significantly associated with poor OS, as were those treated with nivolumab.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a high NLR has been demonstrated to be associated with low overall survival (OS) in patients with solid tumors 13,14 . Therefore, the NLR is a prognostic indicator in patients with NSCLC, 5,15,16 small cell lung cancer, 17,18 and other cancers 19–22 . Specifically, Nathan et al revealed that the NLR is a significant prognostic indicator of survival in patients treated for early‐stage NSCLC with stereotactic radiation 5 .…”
Section: Introductionmentioning
confidence: 99%